NUBPL, a novel metastasis‐related gene, promotes colorectal carcinoma cell motility by inducing epithelial–mesenchymal transition. Issue 6 (14th June 2017) - Wang, Yuhui; Wu, Nan; Sun, Donglin; Sun, Haiming; Tong, Dandan; Liu, Duo; Pang, Bo; Li, Su; Wei, Jia; Dai, Jialin; Liu, Yang; Bai, Jing; et al.
Abstract : Nucleotide binding protein‐like, NUBPL, is an assembly factor for human mitochondrial complex I, which is the biggest member of the mitochondrial respiratory chain. However, the relationship between NUBPL and carcinoma progression remains unknown. In this study, NUBPL was characterized for its role in colorectal cancer (CRC) and the underlying molecular mechanisms. Data ( n  = 197) from the Oncomine database revealed that mRNA levels of NUBPL were remarkably overexpressed in CRC tissues compared with normal tissues. In addition, immunohistochemical analysis of 75 pairs of CRC and non‐tumor tissues showed that the expression level of NUBPL was significantly higher in CRC tissues, and its expression level was positively associated with lymph node metastasis ( P  = 0.028) and advanced staging (P  = 0.030). Expression of NUBPL in metastatic lymph nodes of CRC patients was also detected by immunohistochemical staining and high expression levels of NUBPL were observed. Overexpression of NUBPL significantly promoted the migration and invasion ability of CRC cell lines SW480 and SW620, whereas knockdown of NUBPL lead to an opposite effect. Our further study found that NUBPL could induce epithelial–mesenchymal transition (EMT), characterized by downregulation of epithelial markers (E‐cadherin) and upregulation of mesenchymal markers (N‐cadherin and vimentin). Moreover, NUBPL was able to activate ERK, which is believed to promote EMT and tumor metastasis. Inhibition of ERK suppressed the NUBPL‐induced changes in EMT and cell motility. These data showed that NUBPL plays a vital role in CRC migration and invasion by inducing EMT and activating ERK. It might be a novel therapeutic target for CRC. Abstract : NUBPL plays a vital role in CRC migration and invasion by inducing EMT. It might be a novel therapeutic target for CRC.